2017
DOI: 10.1590/s1679-87592017134406503
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and seasonal variation of microphytoplankton community and the correlation with environmental parameters in a hypereutrophic tropical estuary - Maranhão - Brazil

Abstract: Duarte-dos-Santos et al.: Spatial-seasonal variation of microphytoplankton 356 Spatial and seasonal variation of microphytoplankton community and the correlation with environmental parameters in a hypereutrophic tropical estuary -Maranhão -BrazilThe Bacanga River Estuary has a hydrodynamic behavior and its tidal flow is limited by a dam. It is considered as a hypertrophic environment that receives daily high loads of domestic sewage without treatment. This study aimed to evaluate the spatial and temporal varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
(66 reference statements)
1
4
0
1
Order By: Relevance
“…The ITCZ, during the following months of the year, is much less intense and results in a dry season (Dias et al, 2016;Funceme, 2016). This seasonal pattern was confirmed along the study period and it was in accordance with previous studies for the northeastern region (Azevedo et al, 2008;Rodrigues and Cutrim, 2010;Duarte-dos-Santos et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The ITCZ, during the following months of the year, is much less intense and results in a dry season (Dias et al, 2016;Funceme, 2016). This seasonal pattern was confirmed along the study period and it was in accordance with previous studies for the northeastern region (Azevedo et al, 2008;Rodrigues and Cutrim, 2010;Duarte-dos-Santos et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Studies addressed the dynamics of phytoplankton community in estuaries along the north coast of Maranhão -Brazil, especially in the São Marcos Bay, are scarce (Teixeira et al, 1988;Lavôr-Fernandes, 1988;Azevedo et al, 2008;Rodrigues and Cutrim, 2010;Duarte-dos-Santos et al, 2017). The analysis of the seasonal and tidal distribution of phytoplankton community and the complex relationships of these distribution patterns with environmental factors in the São Marcos Bay can identify potential indicative species of ecological conditions as well as provide relevant scientific evidence to water quality assessment and pollution control.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there have been reports of Euglena blooms occurring in other places. A string of reports on Euglena water blooms in various parts of the world have begun to appear, such as in 17 states in the United States [29,30], Poland (in a shallow oxbow lake) [31], Iran (Gorgan Bay) [32], Brazil (Guaiba Lake and the Bacanga River Estuary) [33,34], and China (Luoma Lake and shallow urban lakes in Wuhan) [35,36]. In retrospect, previous research has generally discussed the effects of other algae on nutrient salt consumption and physiological mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…The response of phytoplankton to these environmental variables differ from estuary to estuary, reaches to reaches and time to time (Lancelot and Muylaert, 2011). Seasonal changes in phytoplankton communities, as well as spatial changes, have been noted (Dalu et al, 2018;Li et al, 2014;Rychtecky and Znachor, 2011;Thompson et al, 2008) although a lack of spatial variability has also been reported (dos Santos et al, 2017).…”
Section: 42: Phytoplanktonmentioning
confidence: 99%
“…In estuarine studies, despite the fast growth rate and short (hours to a few days (Marra, 2002) life spans of phytoplankton cells, shifts and dominance of phytoplankton groups are mostly reported either monthly or seasonally, e.g., in South Africa (Dalu et al, 2018(Dalu et al, , 2014Lemley et al, 2017;Nche-Fambo et al, 2015;Gama et al, 2005) and internationally (Kouhanestani et al, 2019;Muñiz et al, 2018;Dos Santos et al, 2017;Shen et al, 2011). There is very limited information on the phytoplankton temporal variability beyond seasons, especially in South African estuaries.…”
Section: 42: Phytoplanktonmentioning
confidence: 99%